The Examination of “Hood Feminism” Elements in “The Hate U Give” by Angie Thomas (2017). - Chellali, Abir; Naoumi, Mohammed (University of Ammar Theledji -Laghouat, 2021)
Before the 15th century, the European Women were persecuted by male authority, they went through many problems to have their status in society. They could not have their rights, even the simplest rights to live as human beings, they were completely neglected and mistreated by men. They wanted to create a new social movement to voice for their rights, this creation was called Feminism. By the coming of Feminism women’s life changed from being a slave who raised kids and cook for husband to a queen, teacher, artist and author. This dissertation is an analytical work that examines the meaning of Feminism and its important concepts such as the historical highlights, the main wave and the manifestations that the movement had. Moreover, it discusses the Feminist literature and how the Black women message can be seen to the world through literary writings. It also analyses the main elements of the “Hood Feminism in Angie Thomas novel “The Hate U Give”. The main conclusion of this modest work is written to show that the elements of Kendall’s fiction book do exist in Angie Thomas novel which is shown in Racism, murdering Black People and the use of media